2000
DOI: 10.1001/archotol.126.4.473
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD3/Anti-CD28 Bead Stimulation Overcomes CD3 Unresponsiveness in Patients With Head and Neck Squamous Cell Carcinoma

Abstract: A subpopulation of patients with HNSCC who are nonresponders to alphaCD3 stimulation has been identified, showing reduced proliferation and IL-12 and IFN-gamma secretion. Nonresponders stimulated with alphaCD3/alphaCD28 beads reversed immune unresponsiveness and induced a type 1 cytokine response. Bead-generated ATCs from patient 11 in the responder group lysed autologous and allogeneic HNSCC in vitro, suggesting a possible effective immunotherapeutic modality in the treatment of HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
(21 reference statements)
1
14
0
Order By: Relevance
“…5,6 We found that CD3/CD28 costimulation under T1-or T2-promoting conditions yielded greatly increased T-cell expansion compared with CD3 stimulation alone; this result is consistent with the known antiapoptotic role of CD28 signaling to sustain proliferation possibly through the up-regulation of bcl-x L 8 or other molecules. 27 Our finding that CD8 ϩ T cells expanded more than CD4 ϩ T cells under T1 and T2 culture conditions is consistent with the known role of CD28 in CD4 and CD8 activation and the increased capacity of CD8 ϩ T cells to proliferate.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…5,6 We found that CD3/CD28 costimulation under T1-or T2-promoting conditions yielded greatly increased T-cell expansion compared with CD3 stimulation alone; this result is consistent with the known antiapoptotic role of CD28 signaling to sustain proliferation possibly through the up-regulation of bcl-x L 8 or other molecules. 27 Our finding that CD8 ϩ T cells expanded more than CD4 ϩ T cells under T1 and T2 culture conditions is consistent with the known role of CD28 in CD4 and CD8 activation and the increased capacity of CD8 ϩ T cells to proliferate.…”
Section: Discussionsupporting
confidence: 81%
“…1,2 The use of CD3/CD28-generated T cells has been evaluated as a methodology for the cellular immunotherapy of cancer 3 and immuno-augmentation in patients with HIV infection. [4][5][6] The potential application of this approach may reside in the usefulness of CD28 costimulation to promote the generation of a polyclonal T cell receptor repertoire 7 with enhanced effector function. [8][9][10] The successful application of this CD28-based immunotherapy approach will likely require the generation of antigen specificity, either through further in vitro culture or in vivo sensitization.…”
Section: Introductionmentioning
confidence: 99%
“…However, we have previously demonstrated that replacing the initial CD3/IL-2-induced activation by CD3/CD28 mAb-coated beads and IL-2 could prevent the occurrence of TCRBV repertoire alterations. 18 Moreover, CD28 costimulation has been shown to reverse CD3 unresponsiveness 19 and to exert antiapoptotic effects. 20-22 Thus, we tested whether an initial activation by CD3/CD28 beads and IL-2 …”
Section: Loss Of Ebv-reactive Cells Can Be Prevented In Part By An Inmentioning
confidence: 99%
“…Head and neck squamous cell carcinomas (HNSCC) patients are particularly deficient in their immune responsiveness. In one study, T cells from about one-third of HNSCC patients were reported to be unresponsive to stimulation through CD3 [6]. Mitogen-stimulated proliferation by T cells from HNSCC patients diminished with more progressive disease, and decreased T-cell blastogenesis was associated with reduced patient survival [1].…”
Section: Introductionmentioning
confidence: 99%